Design and implement of voltage regulator - Huang, Zheng Long (2019)
Voltage regulators is one of the most widely used electronic component in the electronic world. It is capable of supplying a fixed output voltage when the supply voltage is not constant. This project includes a literature review, which consist of different types of voltage regulators and their working principles. Components such as Zener diode, MC34063 are studied in-depth and implemented in the circuit design in Chapter 3. The two most commonly used voltage regulators are linear and switching voltage regulators. In this project, transistor series voltage regulator, transistor shunt voltage regulator, variable voltage regulator, buck converter, boost converter and buck-boost converter are explored and implemented. The circuit designs are researched and correct component ratings are selected. Next, the circuit designs are simulated in computer software, MultiSIM. The prototypes are implemented and test in the breadboards and PCB (printed circuit board). The simulation and actual results of the circuit designs are recorded in the report. The ideal and actual result of the circuits are compared and analyze.